Kekerasan Simbolik Pada Teks Pemberitaan COVID-19 Di Media Daring Gorontalo - Julianur Rajak Husain; Noval Sufriyanto Talani; Yowan Tamu (Jurnal Kajian Ilmiah, 2023)
The COVID-19 pandemic has become a momentum for global and local mass media to compete to present news about the surge in cases of transmission of coronavirus diseases, including Gorontalo's local online media, Gopos.id. This research was raised from the problem of how the news text of COVID-19 in online media such as Gopos.id is displayed. The purpose of this research is to find out about the discourse on COVID-19 and to identify and find hidden signs of symbolic violence in the news text of COVID-19 on the online media Gopos.id through the use of certain words, phrases, or sentences. News texts are analyzed using qualitative methods with a knife of analysis using semiotics from M.A.K Halliday, which includes (a) the field of discourse, (b) the tenor of discourse, and (c) the mode of discourse. Based on the research results, symbolic violence in COVID-19 reporting texts in the online media Gopos.id tends to appear in discourse fields and discourse modes or language styles and is implicitly presented to the discourse participants. Because symbolic violence is invisible or hidden, victims tend not to realize it.